Tinjauan Yuridis Pengalihfungsian Sebagian Apartemen-Mall X Menjadi Rumah Sakit Rujukan Covid-19 - Jasmine, Geraldine Graviela; Sriwati; Nabbilah Amir (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
The number of Covid-19 cases in Jakarta is increasing every day. This resulted in Covid-19 referral hospital being so full that they were no longer able to accommodate any more patients. The government responded by converting unused buildings into Covid-19 referral hospitals. An entrepreneur, Manager L, the owner of Mall-Apartment X, offered to change the function of one of his buildings. However, he didn't ask for the resident's approval. The method used for this research is the normative juridical method by conducting a literature study on legislation as primary legal materials and literature as secondary legal materials. The action of Manager L can't be justified because the manager didn't ask for the approval of the occupants. Thus the decision to convert the building didn't accommodate the health and comfort aspects of the building. The residents should make complaints so the government can follow up on violations committed by the manager. The manager should be responsible for returning the function of the apartment to its original function. Keywords: Conversion, Apartment, Apartment Manager, Hospital